Korelasi antara Penguasaan Kosakata dengan Kemampuan Menulis Karangan Narasi pada Pelajaran Bahasa Indonesia Siswa Kelas XI SMA Negeri 4 Bengkulu - Kusmaita, Kusmaita (UNIB Press, 2019)
Not all of the ability to write narrative essays from Bengkulu 4 High School students still obtained good criteria. This is thought to be caused by the low mastery of the vocabulary. For this reason, testing of the correlation between vocabulary mastery and narrative essay writing skills is needed. The purpose of this study is to: 1) describe the level of mastery of Indonesian vocabulary, 2) describe the level of narrative essay writing ability, and 3) determine whether there is a significant relationship between mastery of vocabulary mastery with narrative essay writing ability. The research method uses the correlation method. Data collection techniques using technical tests. The test instrument trial then the validity and reliability are calculated. Correlation analysis using the Product Moment formula. The results showed that there was a positive correlation between vocabulary mastery and narrative essay writing ability with a value of 0.724. This is also proved by mastering students 'vocabulary sufficiently and vice versa the results of students' narrative essay writing ability are also categorized sufficiently. This proves that the better the students' vocabulary mastery, the better the ability to write narrative essays.